Radar Emitter Identification Based on Novel Time-Frequency Spectrum and Convolutional Neural Network - Xiao, Zhiling; Yan, Zhenya (IEEE communications letters, 2021)
Radar emitter identification (REI) is significant in both military and civilian application domains. A critical step for REI is signal feature extraction. Most radar emitter signals are non-stationary, and many studies apply time-frequency spectrum features for non-stationary signal analysis in recent years. This letter proposes a novel spectrum calculation method for signal feature analysis using short-time Fourier transform (STFT) and k -means algorithm. We first compute the time-frequency spectrograms of emitter signals by the proposed method. And we apply the convolutional neural network (CNN) for automatic identification based on the time-frequency images. In the experiment, we simulate different emitter signals for performance evaluation and compare our method with the spectrum analysis methods adopted in the literature. The results prove that our method can achieve excellent performance and has strong robustness in the condition of low signal-to-noise ratio (SNR), and our time-frequency analysis method works well in real-time.